Respostas
respondido por:
0
( - 2/3 )² * ( - 2 / 2 )³
4/9 *( - 8 / 27 ) = - 32 / 243
- 2 ( 3 / 2 )³ + 1^15 - ( - 2 )
- 2( 27 / 8 ) + 1 + 2
- 2* ( 27/ 8 ) + 3
- 54 / 8 + 3
- 54 + 3 / 8
- 30 / 8 simplifica por 2 = - 15 / 4
resposta letra e)
4/9 *( - 8 / 27 ) = - 32 / 243
- 2 ( 3 / 2 )³ + 1^15 - ( - 2 )
- 2( 27 / 8 ) + 1 + 2
- 2* ( 27/ 8 ) + 3
- 54 / 8 + 3
- 54 + 3 / 8
- 30 / 8 simplifica por 2 = - 15 / 4
resposta letra e)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás